The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Double germline mutations in APC and BRCA2 in an individual with a pancreatic tumor - Caroline Goehringer; Christian Sutter; Matthias Kloor; Johannes Gebert; Emily P. Slater; Monika Keller; Irmgard Treiber; Petra Ganschow; Martina Kadmon; Ute Moog (Familial Cancer, 2017)

Hepatoblastoma in two siblings and familial adenomatous polyposis: causal nexus or coincidence? - Christina Evers; Harald Gaspar; Matthias Kloor; Gergana Bozukova; Martina Kadmon; Monika Keller; Christian Sutter; Ute Moog (Familial Cancer, 2012)

Relating remotely sensed forest damage data to wind data: storms Lothar (1999) and Vivian (1990) in Switzerland - Tilo Usbeck; Peter Waldner; Matthias Dobbertin; Christian Ginzler; Christian Hoffmann; Flurin Sutter; Charlotte Steinmeier; Richard Volz; Gustav Schneiter; Martine Rebetez (Theoretical and Applied Climatology, 2012)

A comprehensive environmental assessment of petrochemical solvent production - Christian Capello; Gregor Wernet; Jürgen Sutter; Stefanie Hellweg; Konrad Hungerbühler (The International Journal of Life Cycle Assessment, 2009)

A large MSH2 Alu insertion mutation causes HNPCC in a German kindred - Matthias Kloor; Christian Sutter; Nicolas Wentzensen; Friedrich W. Cremer; Annick Buckowitz; Monika Keller; Magnus von Knebel Doeberitz; Johannes Gebert (Human Genetics, 2004)

Juvenile polyposis: massive gastric polyposis is more common in MADH4 mutation carriers than in BMPR1A mutation carriers - Waltraut Friedl; Siegfried Uhlhaas; Karsten Schulmann; Manfred Stolte; Steffan Loff; Walter Back; Elisabeth Mangold; Martin Stern; Hanns-Peter Knaebel; Christian Sutter; Ruthild G. Weber; Steffen Pistorius; et al. (Human Genetics, 2002)